Arts and Academic Achievement―Empirical Evidence for Arts Realities in United States Education Law and Around the World - AnnRené Joseph (International Dialogues on Education: Past and Present, 2019)
That the arts enhance academic achievement has been a claim of educators for the past century. This experimental study examined whether and to what extent the use of creative dramatics interventions increased the vocabulary achievement of fourth grade students in a language arts classroom. The 20-day study was conducted across five weeks of school―for 45 minutes each day―during the normally scheduled language arts instruction block. It included a pretest, 17 consecutive school days of instruction, and a posttest. A retention test was administered five weeks later. Three fourth grade teachers were randomly assigned to a random sample of 83 fourth graders. The study was conducted at a Learning Assistance Program (LAP) reading and math school, in a large rural school district in Washington State. Descriptive statistics were used to describe the demographics of the sample…inferential statistics were used to calculate the differences between groups. (Joseph, 2013/2014, pp. 2-3)